ANALISIS KINERJA SISTEM INFORMASI DENGAN METODE INFORMATION TECHNOLOGY OF BALANCED SCORECARD (STUDI KASUS PADA PT PLN LANGSA) - Roy Sari Milda Siregar (Universitas Teuku Umar, 2016)
This evaluation is crucial to develop a better understanding on whether the new Information System is applicable in supporting the staff duties and work responsibilities.This present study is aimed atevaluating the performance of the Information System based on the end-user’s point of view. This research is a descriptive-quantitative field study. In the data analysis, the framework of Information Technology of Balanced Scorecard was used to the secondary user-level respondents (in total of 19 staff consists of 15 managers, assistants, supervisors and experts) which and consists of four perspectives; they are namely, Corporate Contribution, Stakeholder, Operational Excellence, and Future Orientation. The user satisfaction rate was categorized as low, medium and high level. Based on the analysis, the satisfaction rate as per the ITBSC are as follows: low at 10.5%, medium at 84.2% and high at 5.3%. In general, it was found that user satisfaction rate from the perspective of the secondary user (managerial) 92.8% from the expected rate.Keywords: Information Technology of Balanced Scorecard,user satisfaction, evaluation of information systems.